NILAI-NILAI PENDIDIKAN HINDU DALAM PELAKSANAAN TAWUR KESANGA PADA HARI RAYA NYEPI DI KOTA PALANGKA RAYA - Made Paramarta (Jurusan Dharma Acarya STAHN-TP Palangka Raya, 2021)
Abstrak The process of learning knowledge and skills from generation to generation of sustained through training, research and practice. This process is sustainable based on the level of age, education, and insights that evolved structured with the basis of the progress and improvement of the quality of an individual or a group of high-value without having to dipersentase with numbers. Today, the spiritual and the character became the basic thing in the determination of the grooves education personal so that it is more ethical and religious on the development of the person towards the publication of yourself. The purpose of the ceremony is to maintain the balance of nature. If nature is balanced, then the world mikrocosmos (Bhuana Alit) and makrocosmos (Bhuana Agung) in a balanced state and harminis. Tawur Kesanga ceremony is a ceremony pecaruan done once a year, at the turn of the end of the year Saka precisely at tilem kesanga. Ritual Tawur is implemented in Catuspata (the intersection of the Great) to purify Akasa (Swah Loka), the Atmosphere (Bhuwah loka), and Sarwaprani (Bhur Loka). In the city of Palangka Raya tradition is routinely conducted every year. The purpose of the Tawur Kasanga that Neutralizing negative energy into positive energy so it was natural to be balanced, and harmonious. In practice there are educational values of Hinduism such as the value of the tattwa, the value of moral and ritual value. it interesting to be discussed and thoroughly so that the obtained picture to be concluded. From the conclusion that there can be poured into the writing of the Hindu education values on the tawur kesanga implementation of Nyepi day in Palangka Raya. Values education app developed in this paper that the Value of Spiritual Education, the educational value of knowledge, and education value of skiil. Kata Kunci : The Hindu Education Values, Tawur Kesanga, Nyepi Day